2020
DOI: 10.2196/14282
|View full text |Cite
|
Sign up to set email alerts
|

Improving Maximal Strength in the Initial Postoperative Phase After Anterior Cruciate Ligament Reconstruction Surgery: Randomized Controlled Trial of an App-Based Serious Gaming Approach

Abstract: Background Anterior cruciate ligament reconstruction surgery is one of the most common orthopedic procedures. One of the main factors that influence the outcome is regaining strength in the postoperative phase. Because anterior cruciate ligament reconstruction surgeries are often performed in young patients, we combined the concept of prehabilitation with an app-based serious gaming approach to improve maximal strength postoperatively. Objective Our obj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Two studies investigated the comparison of exergames versus usual rehabilitation care with regard to pain, using the visual analogue scale. Of the two studies included (Ahmed et al, 2020;Gokeler et al, 2014), one reported a significant positive association (Clausen et al, 2020) which was not evidenced in the other study (Ahmed et al, 2020). The difference in grouped means for pain was 0.24 (95% CI = − 1.01 to 1.48; p < 0.75; I2 = 0%).…”
Section: Outcome Measures and Resultsmentioning
confidence: 82%
“…Two studies investigated the comparison of exergames versus usual rehabilitation care with regard to pain, using the visual analogue scale. Of the two studies included (Ahmed et al, 2020;Gokeler et al, 2014), one reported a significant positive association (Clausen et al, 2020) which was not evidenced in the other study (Ahmed et al, 2020). The difference in grouped means for pain was 0.24 (95% CI = − 1.01 to 1.48; p < 0.75; I2 = 0%).…”
Section: Outcome Measures and Resultsmentioning
confidence: 82%
“…Exergaming is well-tolerated with few adverse effects and is associated with improved adherence and motivation; however, most existing exergames are serious games emphasizing a specific physical movement or activity. 17–19,31,32 In contrast, our game is more fun and entertainment-focused, allowing patients to strengthen their muscles by using surface electromyography signals as game input without having to mentally focus on exercising. Furthermore, our therapeutic gaming platform may enhance patient engagement and motivation compared to simple visual biofeedback of muscle activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the former, the patient attends to a game on the tablet, rather than their body part, to control a flight course of an airplane with the aim to destroy balloons. 62 The second assumption is that once one starts to transition into the late rehabilitation phase, adding aspects to the environment (e.g., hurdle, ball, or an unstable surface) leads to a shift to an external focus of attention. 22 However, adding environmental factors do not shift the patient's attention to an external focus but simply refer to objects in the environment and not one's intended movement effect.…”
Section: Stages Of Learningmentioning
confidence: 99%